Fiscal Deficits and Inflation in Ghana - Obeng, Solomon Hanson; Abotsi, Anselm Komla (International Journal of Economics and Financial Issues, 2024)
The Ghanaian economy has been faced with persistent fiscal deficits over the years and this affects other macroeconomic variables like inflation. This study therefore empirically examines the effect of fiscal deficit on inflation in Ghana. The study deployed a quantitative research design technique, the Autoregressive Distributed Lag (ARDL) cointegration test, and vector error correction models using annual data spanning 1976 to 2019 with 44 observations. Findings revealed that there is a significant and negative short and long-run relationship between fiscal deficits and inflation in Ghana, with unidirectional causality running from inflation to fiscal deficit. The study recommends that the Government of Ghana should endeavour to finance fiscal deficits mostly through external sources and non-banking methods like the issuance of bonds at the foreign financial market since non-banking borrowing has low inflationary effects.